Equine colic: literature review - Janaina da Silva; Antônio Eurico Vieira Travassos (Universidade Estadual de Alagoas, 2021)
The objective of this article was to review the available literature on equine colic, highlighting general aspects ofthe disease. Horses have anatomical peculiarities in their digestive system, the species is predisposed to severe morphophysiological changes, responsible for signs of severe abdominal pain, known as colic or acute abdomen. Colic syndrome is a frequent cause of death in horses, considered as one of the main diseases requiring veterinary care; the economic losses caused by the disease are significant, as they often imply high costs with the treatment and death of animals. The main causes are gastric problems, dietary changes, low quality food, aerophagia, physical characteristics, parasites among others. Faced with this problem, the faster the diagnosis, the greater the animal's chance of surviving. There are several parameters that should and are evaluated,such as: degree of pain, abdominal distension, heart rate, respiratory and pulse characteristics, coloration of mucous membranes, capillary filling time, rectal temperature, gastrointestinal motility, gastric reflux, findings on palpation rectal, hematocrit, plasma concentration of total proteins, characteristics of peritoneal fluid, transabdominal ultrasound, etc. Given the above, it can be concluded that the picture of colic syndrome has multifactorial origins and that diagnosis and treatment is of paramount importance for reversing the picture and early diagnosis is essential to promote the health and well-being of the animal. Treatment is carried out with specific medications and prevention is always the best alternative.